Antileishmanial Effect of 5,3´ -Hydroxy-7,4´ -dimethoxyflavanone of Picramnia gracilis Tul. (Picramniaceae) Fruit: In Vitro and In Vivo Studies (2015)
ABSTRACT: Species of Picramnia genus are used in folk medicine to treat or prevent skin disorders, but only few species have been studied for biological activity and chemical composition. P. gracilis Tul. is a native species from Central and South America and although its fruits are edible, phytochemical analysis or medicinal uses of this species are not known. In the search of candidates to antileishmanial drugs, this work aimed to evaluate the antileishmanial activity of P. gracilis Tul. in in vitro and in vivo studies. Only ethanolic extract of fruits showed leishmanicidal activity. The majoritarian metabolite was 5,3′-hydroxy-7,4′-dimethoxyflavanone ether that exhibited high activity against L. (V.) panamensis (EC50 17.0 + 2.8 mg/mL, 53.7 μM) and low toxicity on mammalian U-937 cells, with an index of selectivity >11.8. In vivo studies showed that the flavanone administered in solution (2 mg/kg/day) or cream (2%) induces clinical improvement and no toxicity in hamsters with CL. In conclusion, this is the first report about isolation of 5,3′-hydroxy-7,4′-dimethoxyflavanone of P. gracilis Tul. The leishmanicidal activity attributed to this flavanone is also reported for the first time. Finally, the in vitro and in vivo leishmanicidal activity reported here for 5,3′-hydroxy-7,4′-dimethoxyflavanone offers a greater prospect towards antileishmanial drug discovery and development.